MAPPING OF BENTHIC HABITAT IN BAIR ISLAND USING ALLEN CORAL ATLAS DATA - Teurupun, Gafli Luter; Lodar, Stevani; Rahaket, Emelliana; Awayal, Dion Dollan (Jurnal Perikanan Unram, 2025)
Benthic habitat mapping in Bair Island, Southeast Maluku Regency, Maluku Province is the first step in the management and conservation of marine ecosystems that need to be improved. This study aims to map and calculate the extent of benthic habitat around Bair Island by utilizing Allen Coral Atlas (ACA) data. The methods used include multispectral satellite image analysis by performing atmospheric correction, water column correction and sun glare removal. Benthic habitats mapped included coral reefs, seagrasses, microalgae, dead corals and other substrates such as rocks and sand. The results showed that coral reefs dominated the coastal area of Bair Island with an area reaching 53,9 ha, seagrasses 8,4 ha and microalgae 9,8 ha and area of rubble 8,8 ha followed by the dominance of rocks 118 ha as well as sand 98,8 ha. The utilization of ACA data proved effective in providing accurate spatial information with high resolution, so that it can support ecosystem-based management on Bair Island